1999
DOI: 10.1046/j.1523-1755.1999.00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Free-radical–generated F2-isoprostane stimulates cell proliferation and endothelin-1 expression on endothelial cells

Abstract: These studies expand the potential scope of the pathophysiologic significance of F2-isoprostanes, released during oxidant injury, to include alteration of endothelial cell biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
1
7

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 12 publications
5
98
1
7
Order By: Relevance
“…8-iso PGF 2␣ can be generated by a non-enzymatic oxidative reaction of arachidonic acid (28,29). Measurements of 8-iso PGF 2␣ have been used to quantitate oxidative stress in vitro and in vivo (15,17,39). We demonstrated that the renal excretion of 8-iso PGF 2␣ was increased in the mice infused with AngII400.…”
Section: Discussionmentioning
confidence: 90%
“…8-iso PGF 2␣ can be generated by a non-enzymatic oxidative reaction of arachidonic acid (28,29). Measurements of 8-iso PGF 2␣ have been used to quantitate oxidative stress in vitro and in vivo (15,17,39). We demonstrated that the renal excretion of 8-iso PGF 2␣ was increased in the mice infused with AngII400.…”
Section: Discussionmentioning
confidence: 90%
“…34 Other biological effects of 8-epi-PGF 2a are those on muscle vascular cells and on endothelial cells in which DNA synthesis and cell proliferation is stimulated. 33,35 These effects also are probably due to activation of receptors related to TXA 2 r. Finally, 8-epi-PGF 2a seems to mediate the increased production of TGF-b1 in kidney mesangial and glomerular cells exposed to high ambient glucose such as that produced by streptozotocin-induced diabetes. 36 Therefore, it seemed likely that HSC, which have been reported to respond to lipid peroxidation products, could be activated by F 2 -isoprostanes, the direct derivatives of arachidonic acid.…”
Section: Discussionmentioning
confidence: 98%
“…[42][43][44][45] Hydrogen peroxide and superoxide can increase ET-1 synthesis, and 8-iso prostaglandin F2ϰ, a product formed by free radical catalyzed lipid peroxidation, also can have similar effects. 42 The relevance of these observations is unclear given that Saito et al observed contrasting findings that hydrogen peroxide actually decreases ET-1 mRNA and protein synthesis in endothelial cells. 46 It remains possible that increased production of oxygen-derived free radicals could provide a mechanism for Ang II-induced ET-1 synthesis, although this possibility has yet to be investigated.…”
Section: Et-1 and Oxidative Stressmentioning
confidence: 99%
“…40,41 Whereas ET-1 can increase oxidative stress, there are a number of reports that reactive oxygen species can increase ET-1 production in cultured endothelial cells and vascular smooth muscle cells. [42][43][44][45] Hydrogen peroxide and superoxide can increase ET-1 synthesis, and 8-iso prostaglandin F2ϰ, a product formed by free radical catalyzed lipid peroxidation, also can have similar effects. 42 The relevance of these observations is unclear given that Saito et al observed contrasting findings that hydrogen peroxide actually decreases ET-1 mRNA and protein synthesis in endothelial cells.…”
mentioning
confidence: 99%